2013
DOI: 10.1002/pca.2435
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cleistopholis patens Leaf and Trunk Bark Oils Using Combined GC‐ Flame Ionisation Detection, GC‐Retention Index, GC–MS and 13C‐NMR

Abstract: Combined analysis of essential oil including (13) C-NMR without isolation of the components, appeared really efficient to identify and quantify germacrene isomers and in parallel elemene isomers in essential oils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
(27 reference statements)
3
18
0
Order By: Relevance
“…More precisely, the contents of germacrene isomers were under‐evaluated (GeA = 0.3%, GeB = 9.2%, GeC = not found), while the contents of elemene isomers were over‐evaluated ( β ‐E = 23.8%, γ ‐E = 7.1%, δ ‐E = 1.2%). Indeed, we have demonstrated in a previous work that germacrene isomers contained in essential oils rearranged partially or totally during GC analysis into the corresponding elemene isomers, following a thermal sigmatropic rearrangement . Therefore, the content of every compound was calculated using a combination of GC‐FID and 13 C‐NMR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, the contents of germacrene isomers were under‐evaluated (GeA = 0.3%, GeB = 9.2%, GeC = not found), while the contents of elemene isomers were over‐evaluated ( β ‐E = 23.8%, γ ‐E = 7.1%, δ ‐E = 1.2%). Indeed, we have demonstrated in a previous work that germacrene isomers contained in essential oils rearranged partially or totally during GC analysis into the corresponding elemene isomers, following a thermal sigmatropic rearrangement . Therefore, the content of every compound was calculated using a combination of GC‐FID and 13 C‐NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have demonstrated in a previous work that germacrene isomers contained in essential oils rearranged partially or totally during GC analysis into the corresponding elemene isomers, following a thermal sigmatropic rearrangement. [19] Therefore, the content of every compound was calculated using a combination of GC-FID and 13 C-NMR. Firstly, the percentages (GC-FID) of GeA and b-E on the one hand, those of GeB and c-E on the other hand, were summed.…”
Section: Analysis By Combination Of Chromatographic and Spectroscopicmentioning
confidence: 99%
“…Moreover, frequently these compounds have a very close RI and therefore their identification by GC‐MS in combination with RIs remains a difficult task. Identification of individual components of a natural mixture by GC‐MS is also difficult if not impossible for compounds that co‐elute on the GC columns at our disposal and for heat sensitive compounds that rearrange on the injector or on the GC column during the analysis . The worst occurs when the MS data of an essential oil component are not compiled in the computerized libraries that simultaneously contain spectra of other compounds exhibiting similar fragmentations.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our on‐going work on the characterization of aromatic plants of the Ivory Coast through the chemical composition of their essential oils, we conducted this study on the leaf oil from P. longifolia . In this paper we highlight the key role of 13 C nuclear magnetic resonance (NMR) (in combination with column chromatography) in the identification of oxygenated sesquiterpenes whose mass data are not compiled in commercial computerized mass spectrometry (MS) libraries.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, no study has been reported in the literature on the chemical composition of P. oliveri essential oil. Within our ongoing work on the characterization of Ivoirian aromatic plants through the chemical composition of their essential oils , we were interested in P. oliveri leaf oil. The first analyses exhibited a complex essential oil with a composition dominated by sesquiterpenes.…”
Section: Introductionmentioning
confidence: 99%